Sustainable Tourism Management Strategy in the Lovina Beach Coastal Area, Kalibukbuk Village Through MICMAC Systemic Analysis - Ni Ketut Catur Wulandari; I Putu Ananda Citra; I Gede Budiarta (International Journal Labs, 2026)
This research aims to analyze sustainable tourism management strategies in the Lovina Beach Coastal Area, Kalibukbuk Village, Buleleng Regency, using the MICMAC (Matrix of Cross Impact Multiplications Applied to a Classification) systemic analysis approach. The study employs a quantitative descriptive approach with a systemic perspective, involving ten key respondents representing the Pentahelix stakeholders. Data were collected through MICMAC questionnaires, in-depth interviews, and field observations, and subsequently analyzed using MICMAC software to map the levels of influence and dependence between variables within the coastal tourism management system. The results indicate that Coastal Waste Management, active Community Participation, and Equitable Distribution of Economic Benefits from tourism serve as primary driving variables within the system. Community-based tourism and the Quality of the Coastal Environment act as linkage variables, while the Effectiveness of the Area Management System falls into the dependent variable category. These findings emphasize that the strategic and systemic strengthening of driving variables, coupled with improved coordination among stakeholders, is the primary key to achieving sustainable tourism management in the Lovina Beach Coastal Area.